2006
DOI: 10.1261/rna.2307206
|View full text |Cite
|
Sign up to set email alerts
|

The La protein functions redundantly with tRNA modification enzymes to ensure tRNA structural stability

Abstract: Although the La protein stabilizes nascent pre-tRNAs from nucleases, influences the pathway of pre-tRNA maturation, and assists correct folding of certain pre-tRNAs, it is dispensable for growth in both budding and fission yeast. Here we show that the Saccharomyces cerevisiae La shares functional redundancy with both tRNA modification enzymes and other proteins that contact tRNAs during their biogenesis. La is important for growth in the presence of mutations in either the arginyl tRNA synthetase or the tRNA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 53 publications
(71 reference statements)
4
71
0
2
Order By: Relevance
“…For example, Lhp1p becomes required for accumulation of the U6 spliceosomal snRNA when yeast contain mutations in the Lsm2-Lsm8 proteins that are components of the mature RNP (4,5). For pre-tRNAs, both modifications and binding to subsequent proteins such as synthetases likely contribute to maintaining correct folds in vivo, because Lhp1p is important for growth when yeast contain mutations in either the arginyl-tRNA synthetase or the tRNA modifying enzyme TRM1 (29). Consistent with a redundant function in stabilizing tRNA structure, Trm1p catalyzes dimethylguanosine formation at position 26 in many tRNAs, a modification that prevents formation of alternate anticodon stems (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Lhp1p becomes required for accumulation of the U6 spliceosomal snRNA when yeast contain mutations in the Lsm2-Lsm8 proteins that are components of the mature RNP (4,5). For pre-tRNAs, both modifications and binding to subsequent proteins such as synthetases likely contribute to maintaining correct folds in vivo, because Lhp1p is important for growth when yeast contain mutations in either the arginyl-tRNA synthetase or the tRNA modifying enzyme TRM1 (29). Consistent with a redundant function in stabilizing tRNA structure, Trm1p catalyzes dimethylguanosine formation at position 26 in many tRNAs, a modification that prevents formation of alternate anticodon stems (30).…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal anti-Nop1p was a gift of J. Aris (University of Florida, Gainesville). Northern blotting was as described (29). To examine aminoacylation, RNA was extracted at low pH and fractionated in acidic polyacrylamide gels (33).…”
Section: Methodsmentioning
confidence: 99%
“…Analyses of the mutant strains revealed that La stabilizes nascent U6 snRNAs when cells contain mutations in components of the Lsm2-Lsm8 ring (Pannone et al 1998(Pannone et al , 2001) and that La assists assembly of the U4 snRNA into the U4/U6 snRNP when cells contain a mutation in the snRNP core protein Smd1p (Xue et al 2000). La is also important for growth when cells contain mutations in the arginyl tRNA synthetase or either of two tRNA modification enzymes, Trm1p and Trm61p (Calvo et al 1999;Copela et al 2006). Taken together, these experiments suggest that La functions redundantly with other proteins that contact nascent RNAs to stabilize these RNAs and assist their assembly into functional RNPs.…”
Section: La Stabilizes Nascent Noncoding Rnas and Assists Pre-trna Fomentioning
confidence: 99%
“…In addition to the requirement for La, the trr4-1 mutation causes a fraction of the mutant tRNA to be unstable. Degradation of the mutant tRNA does not require the Trf4 polymerase (Copela et al 2006). (B) Methylation of adenosine 58 is required for stable accumulation of tRNA i Met .…”
Section: Sm-like Protein Rings May Facilitate Rna-rna Interactionsmentioning
confidence: 99%
See 1 more Smart Citation